2018
DOI: 10.1016/j.aninu.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lecithin improves feed efficiency without impacting meat quality in immunocastrated male pigs and gilts fed a summer ration containing added fat

Abstract: The aim of this study was to investigate the effects of sex and dietary lecithin on growth performance, meat quality, muscle collagen content and gene expression of key genes involved in collagen synthesis in finisher pigs. A total of 256 pigs (Large White × Landrace) were allotted to a 2 × 2 factorial arrangement involving sex (gilt or immunocastrated [IC] male) and dietary treatment (0 or 5 g/kg of dietary lecithin). All diets were formulated to contain 4.6% tallow with relatively high total fat of 6.3%. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Variation in meat characteristics caused by gender can be explained by gender's influence on protein and body fat depositions [29]. Regarding the physicochemical traits (Table 1), the gilts in this study had greater IMF than castrates (2.68% vs. 2.22%).…”
Section: Gender Effectsmentioning
confidence: 71%
“…Variation in meat characteristics caused by gender can be explained by gender's influence on protein and body fat depositions [29]. Regarding the physicochemical traits (Table 1), the gilts in this study had greater IMF than castrates (2.68% vs. 2.22%).…”
Section: Gender Effectsmentioning
confidence: 71%
“…26,27 However, phosphatidylcholine has not been extensively studied in beef cattle. Certainly, dietary supplementation with lecithin improves the feed conversion rate in pigs on a high-fat diet during finishing period, 28 and rumen-protected choline supplementation has been shown to promote weight gain and improve meat quality in young lambs. 29 In addition, differential gene expression and transcripts already highlighted the importance of phospholipids metabolism in cattle feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the supplementation of rumen-protected choline (as a precursor of phospholipids) reduced triacylglycerol accumulation in the liver and increased milk yield during the transition period in dairy ruminants. , However, phosphatidylcholine has not been extensively studied in beef cattle. Certainly, dietary supplementation with lecithin improves the feed conversion rate in pigs on a high-fat diet during finishing period, and rumen-protected choline supplementation has been shown to promote weight gain and improve meat quality in young lambs . In addition, differential gene expression and transcripts already highlighted the importance of phospholipids metabolism in cattle feed efficiency. , Despite dietary phospholipids are extensively degraded by the rumen and PC concentration depends almost exclusively upon endogenous synthesis, understanding of the requirements of PC is needed to improve feed efficiency in beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Attia et al (2018) investigated that supplementation with 1% or 1.5% soya lecithin improved rabbit growth performance and fat digestibility in both summer and winter. Additionally, Akit et al (2018) reported that lecithin improved feed efficiency in finishing pigs without impacting pork quality.…”
Section: Introductionmentioning
confidence: 99%